2017
DOI: 10.4244/eij-d-17-00345
|View full text |Cite
|
Sign up to set email alerts
|

Predicting the infarct-related artery in STEMI from the surface ECG: independent validation of proposed criteria

Abstract: Existing ECG criteria to predict the IRA in STEMI have modest diagnostic performance when externally validated, and lower than in the original reports. Distinguishing the level of obstruction in the left anterior descending artery remains especially challenging. Hence, their use should be pragmatic when selecting an initial catheter for treating STEMI, since discordances will occur when compared to the actual angiogram.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…In our case, successful cannulation of both left and right coronary ostium was achieved despite a severe RAS. Standard 12 lead ECG has modest diagnostic accuracy for identifying the infarct-related artery [6]. A dedicated radial catheter can correctly identify the culprit vessel, more importantly in the setting of inferior myocardial infarction.…”
Section: Discussionmentioning
confidence: 99%
“…In our case, successful cannulation of both left and right coronary ostium was achieved despite a severe RAS. Standard 12 lead ECG has modest diagnostic accuracy for identifying the infarct-related artery [6]. A dedicated radial catheter can correctly identify the culprit vessel, more importantly in the setting of inferior myocardial infarction.…”
Section: Discussionmentioning
confidence: 99%
“…10,11 Severe LAD obstruction causes myocardial ischaemia and angina. 12 When coronary flow is compensated by the collateral circulation, repolarization abnormalities caused by reperfusion injury result in T-wave symmetrical inversion or biphasic T-waves in the precordial leads. 10 A study conducted by Migliore et al, 13 showed that myocardial oedema rather than stunning and reperfusion of the myocardium underlies the ECG changes of Wellens' syndrome.…”
Section: Discussionmentioning
confidence: 99%
“…Likewise, when ST depression (STD) in aVL derivation is higher than DI derivation (aVL> DI) culprit artery is more likely to be RCA. [7][8][9][10] Diagnosis of inferior STEMI was made in patients with ST-segment elevation of more than 1 mm in at least two of DII, DIII or aVF derivations. 5 In patients with ST-segment depression in V1 and V2, posterior leads were placed and V7-9 obtained in order to diagnose concomitant posterior STEMI.…”
Section: Ecg Criteriamentioning
confidence: 99%